Economic Valuation of Knowledge-Based Capital: An International Comparison - Hofman, A (Elsevier Inc., 2019)
This chapter uses an alternative approach to measuring the knowledge intensity of economies to those commonly uses that are based on the aggregation of industries according to selected indicators such as R&D expenditure or labor force skills. We follow an economic approach rooted in growth accounting methodology, determining the contribution of each individual factor (capital and labor) according to the prices of the services it provides. This methodology is applied to six American countries (the United States, Canada, and four Latin-American countries, namely Brazil, Chile, Colombia, and Mexico) and five European countries (France, Germany, Italy, Spain, and the United Kingdom). The analysis covers the period 2000-15. © 2020 Elsevier Inc. All rights reserved.